The Châtelperronian conundrum: Blade and bladelet lithic technologies from Quinçay, France. Issue 95 (June 2016) - Roussel, M.; Soressi, M.; Hublin, J.-J.
Abstract: The discovery of an almost complete Neanderthal skeleton in a Châtelperronian context at Saint-Césaire 35 years ago changed our perspective on the beginning of the Upper Paleolithic in western Europe. Since then, the Châtelperronian has generally been considered a "transitional" industry rather than an Upper or a Middle Paleolithic industry because of its chronological position, and the association of Neanderthal remains with blades, bone tools and personal ornaments. Several competing hypotheses have been proposed to explain the association between Neanderthals and these types of artefacts including post-depositional mixing, acculturation from anatomically modern human populations, or an independent technological evolution by local Neanderthal populations. Quinçay Cave is the only Châtelperronian site where personal ornaments have been found that does not contain an overlying Upper Paleolithic layer. This means that the post-depositional mixing of later elements into the Châtelperronian may not be used as an explanation for the presence of these materials. We report here on a detailed technological analysis of lithic artefacts from the three Châtelperronian layers at Quinçay Cave. We compare our results with the technology of Mousterian blade industries dating to OIS (oxygen isotope stage) 5, the Mousterian of Acheulian Tradition type B, and the Proto-Aurignacian. We show that the Châtelperronian is sufficiently divergent from the Middle Paleolithic to be classified as a fully Upper Paleolithic industry, with a focus on blade and bladelet production. We also show that the Quinçay Châtelperronian includes retouched bladelets that resemble those found in the Proto-Aurignacian, but were produced in a different manner. We argue that a technological convergence cannot account for these behaviors, since the specific type of retouched bladelet associated with the Châtelperronian was also regularly used by Proto-Aurignacian of neighboring regions. We suggest that the idea of retouched bladelets may have diffused from the northern Proto-Aurignacian to the Quinçay Châtelperronian and that the transmission of the morphology of this desired end-product without the transmission of its manufacturing process may point toward a low degree of social intimacy between these groups. We conclude that the apparent paradox of the Châtelperronian is the result of the complexity of interaction between Neanderthal and anatomically modern human groups in western Europe between 45, 000 and 40, 000 years ago.